"n Bestuurshulpmiddel vir doelmatige en doeltreffende kerkbestuur: "n Generiese perspektief vir "n makro-gemeente - Berg, A. A. van den (HTS teologiese studies, 2003)
A management tool for efficient and effective church management: A generic perspective for a macro-congregationThis article examines the place and function of project management as a generic management tool in the church and the potential solution it has to offer in respect of congregation management and ministry. "Project" and "project management" are defined and contextualised within a church environment. The project management process is put in the context of a project management system and of the congregation and its relevant functions. Project management consists of five generic phases namely, project initiation, project planning, project execution, project control and project closure. The project manager is provided with an overall picture of the project management process, with specific reference to its compilation and workings. The discussion in the article includes the management of the human dimension of the project management process.